The possibilities of clindamycin and butoconazole containing vaginal cream in reducing the risk of recurrence of urogenital candidiasis in comorbid patients with bacterial vaginosis - G.S.Sergiyenko; T.V.Tazina; M.V.Zhuchkov (IP Berlin A.V., 2018)
Purpose - a study of the efficacy of clindamycin cream with butoconazole (Clindacin B prolong) in the treatment of urogenital candidiasis in combination with bacterial vaginosis (BV) in women of reproductive age outside of pregnancy, the study of the potential of Clindacin B prolong in reducing the risk of recurrence of urogenital candidiasis in comorbid patients with BV. Material and methods. The study included 53 patients aged 18 to 45 years (mean age 31.5±9.4 years) with urogenital candidiasis in combination with BV. All women underwent antibacterial therapy with Clindacin B prolong at 1 dose (5.0 g) in the vagina at night for 3 days. Results. After 3-day therapy with Clindacin B prolong, a 100% cure effect has been achieved, both clinically and laboratory-wise. Then the patients were observed for 6 months. The relapse rate was 10.2%. The conclusion. The clinical efficacy of clindamycin cream with butoconazole (Clindacin B prolong preparation) in the treatment of urogenital candidiasis in combination with BV in women of reproductive age outside of pregnancy was 89.8% with observation for 6 months.